Rewilding the Atlantic Forest: Restoring the fauna and ecological interactions of a protected area - Fernandez, Fernando A.S. (2017)
The loss or reduction of animal populations and consequent extinction of ecological interactions in Neotropical forests demand urgent conservation initiatives to reverse these trends. One of the rainforests with the highest levels of mammal defaunation is the Brazilian Atlantic Forest. Local mammalian extinctions in the biome were evaluated to set out priorities. Researchers, reserve managers and ex situ animal keepers throughout the Atlantic Forest were connected through a reintroduction network. From 2010 to 2017, we reintroduced two important seed dispersers, the red-humped agouti and the brown howler monkey, in Tijuca National Park, Rio de Janeiro, with other species on their way. We monitored the reintroduced populations regarding demography, spatial patterns, diet and their effect on ecological interactions. They interacted with several plant species, including large-seeded ones. We found 25 dung beetles’ species interacting with howlers’ feces. As TNP lacked medium and large sized frugivores, the increased dispersal can have a disproportional effect on forest regeneration. Among the main constraints for refaunation programs we pointed out delays to obtain environmental licenses, scarcity of source populations and difficulties regarding quarantine, release and monitoring of the animals. Refaunation has shown promise as a low-cost, effective way to restore ecological processes in defaunated Neotropical forests.